An acoustic 3D positioning system for robots operating underground - Malik,S; O'Sullivan,C; Reddyhoff,T; Dini,D; Holmes,A (IEEE Sensors Letters, 2022)
Underground robots are potentially helpful in many application domains, including geotechnical engineering, agriculture, and archaeology. One of the critical challenges in developing underground robotics is the accurate estimation of the positions of the robots. Acoustic-based positioning systems have been explored for developing an underground 3D positioning system. However, the positioning range is limited due to attenuation in the medium. This letter proposes an underground positioning system that utilizes a novel and easy-to-implement electronic approach for measuringthe acoustic propagation times between multiple transmitters and a receiver. We demonstrate a prototype using four transmitters at the surface and a single buried acoustic sensor as a proof-of-concept. The times of arrival for signals emitted by the different sources are measured by correlating the transmitted and received signals. The distances between the multiple transmitters and a receiver are estimated, and a tri-linearization algorithm is used to estimate the position of the buried sensor in 3D with respect to reference coordinates. The system is tested in a soil tank. The experimental results show that the proposed system is able to estimate the 3D position of buried sensors with an error of less than ±2.5 cm within a measurement field of size 50 cm × 50 cm × 35 cm in X, Y, and Z (width × length × depth). The proposed electronic synchronization approach allows increasing the positioning range of the system by increasing the number of transmittersat the surface. This paves the way for the development of a positioning system for robots operating underground.